Pengaruh Strategi Think Pair Share Berbantuan Index Card Match Terhadap Hasil Belajar IPA di SD Negeri 058295 Benteng Sari - Mutia, Nur Balqis; Utami, Noni Shinta; Jelita, Jelita (Al-Azkiya: Jurnal Pendidikan MI/SD, 2024)
This study aims to determine the effect of think pair share learning strategy assisted by index card match on student learning outcomes in the 2023/2024 academic year at SD Negeri 058295 Benteng Sari. This research is a quasi experiment research with one group pretest-posttest design. The research was conducted in class V of SD Negeri 058295 Benteng Sari in the odd semester of the 2023/2024 school year with a total of 30 students. Data collection techniques were carried out using essay questions to measure student learning outcomes. Data analysis was carried out by statistical analysis of paired sample t-tests. Based on the results of the study obtained a significance value of 0.001. The value is smaller than 0.05 so Ha is accepted and H0 is rejected. The results of this study indicate that there is a significant difference in the think pair share learning strategy assisted by learning media index card match on student learning outcomes at SD Negeri 058295 Benteng Sari. So it can be concluded that the think pair share learning strategy assisted by index card match media can significantly improve student learning outcomes. Thus, this strategy can be applied in elementary schools to improve students' understanding and academic achievement.